Bone-Specific Alkaline Phosphatase as a Complementary Diagnostic Marker for the Assessment of Children and Adolescents with Secondary Osteoporosis - Eunha Bae; Soo Yeun Sim; Su Jin Park; Sung Eun Kim; Seulki Kim; Shin-Hee Kim; Won Kyoung Cho; Kyoung Soon Cho; Min Ho Jung; Byung-Kyu Suh; Moon Bae Ahn (Diagnostics)
Background/Objective: With increasing cases of osteoporosis in children and adolescents, the need for timely diagnosis, management, and follow-up has become important. This study aimed to determine whether bone turnover markers (BTMs), particularly serum bone-specific alkaline phosphatase (BsALP) and serum C-telopeptide of collagen type 1 (CTx), accurately reflect BMD. Methods: In this retrospective study, 280 post-puberty males and females who were previously diagnosed with hemato-oncologic, rheumatic, gastrointestinal, and endocrinologic diseases at a single tertiary care center were reviewed. The association between the lumbar spine bone mineral density (LSBMD) Z-scores and BTMs, such as BsALP and CTx, were assessed. The LSBMD was measured in the anterior–posterior direction using DXA, and BTMs were determined using the blood samples obtained. Results: Of the 280 patients, 95 were male (33.9%), and the mean age was 15.4 <semantics>±</semantics> 2.07 years. With multivariate regression analysis, LSBMD Z-scores and BsALP showed a negative correlation with p < 0.007, while CTx was not statistically significant. The logistic regression models showed that after adjusting for underlying diseases and sex, as BsALP increased, the probability of LSBMD Z-score being ≤−2 increased with an odds ratio of 1.043 (p = 0.048). When comparing BTMs with vertebral fracture while adjusting for underlying diseases and sex, as BsALP increased, the probability of vertebral fracture increased with an odds ratio of 1.035 (p = 0.005). Conclusions: The positive correlation between BsALP and LSBMD Z-scores being ≤−2, as well as with vertebral fracture after adjusting for underlying diseases and sex, suggests the possible application of BsALP as a predictor of bone health in patients.